Multifrequency bioimpedance by spectroscopy vs. routine methods in the management of hydration status in peritoneal dialysis patients: A randomized control trial - Costa, Fabiana Lourenço; Reis, Nayrana Soares do Carmo; Reis, Fabricio Moreira; Oliveira, Rogério Carvalho de; Zanati Bazan, Silméia Garcia; Canedo da Silva, Maryanne Zilli; Martin, Luis Cuadrado; Barretti, Pasqual (Frontiers in Medicine, 2022)
Background: Overhydration (OH) is common in peritoneal dialysis (PD) and increases the cardiovascular risk. Multifrequency bioimpedance spectroscopy (BIS) has been proposed to estimate the hydration in dialysis. Our objective was to evaluate if BIS is superior than control based on clinical assessment plus single-frequency bioimpedance (SF-BIA) on the fluid control and intermediate cardiovascular outcomes. Methods: Randomized controlled study in adult PD patients, with a nine-month follow-up, allocated into two groups: control and BIS. Data were collected from medical records. SF-BIA and BIS, laboratory exams, ambulatory blood pressure monitoring, echocardiography and pulse wave velocity were evaluated. The BIS data were available to the medical team only in BIS group. Results: 34 patients completed the study, 17 in each group. At the endpoint the BIS goup had a significant (p<0,05) greater proportion of patients with OH/ extracellular water (OH/ECW%) ≤ 15% than the control (94,1% vs 52,9%), and a lower OH mean (2,1 ± 1,6 vs 0,9 ± 1,1 L). The control group has a significant increase in the tumor necrosis factor alpha median concentration from baseline to six [11,9 (6,0 - 24,1) vs 44,7 (9,4 - 70,6) pg/ml] and nine months [11,9 (6,0 - 24,1) vs 39,4 (27,9 - 62,6) pg/ml], and in the N-terminal fragment of pro-B-type natriuretic peptide median [239 (171,5 - 360,5) vs 356 (219 - 1555) pg/ml ]. For cardiovascular parameters, BIS group presented a significant reduction in radial PWV [7,7 (6,9 - 9,2) vs 6.5 (5,5 - 8,4) m/s] at nine month, while in the control presented a significant increase in mean central systolic blood pressure (BP) (106,8 ± 11,2 vs 117,6 ± 16,5 mmHg) and in central diastolic BP (90, 4 ± 9,8 vs 103,3 ± 12,5 mmHg) at nine months. The left ventricular mass (LVM)/body surface presented a significant reduction in the control (109,6 ± 30,8 vs 101,2 ± 28,9 g/m²) and BIS group (107,7 ± 24,9 vs 96,1 ± 27,0 g/m²) at nine months. Conclusions: The results suggest BIS is superior than the clinical evaluation plus SF-BIA for the fluid control of PD patients.